Biobank Governance: The Cautionary Tale of Taiwan Biobank - Shawn H.E. Harmon; Shang-Yung Yen; Shu-Mei Tang (SCRIPTed: A Journal of Law, Technology & Society, 2018)
The importance of biobanks has long been mooted, and multiple models of development and operation can be found as a result of many actors founding biobanks (from institutions starting disease-specific banks to governments starting national population biobanks). Many countries began developing biobanks in the absence of national policies to aid in that formation. Taiwan was one such country. Believing that the unique genetic makeup, distinctive lifestyles, and disease-causing factors of the Taiwanese people deserved study, Taiwan took steps to create Taiwan Biobank. This paper examines Taiwan Biobank’s development and governance and focuses on two matters in particular which generated consternation during the development of Taiwan Biobank: the position adopted in relation to autonomy and ethnicity; and the approach toward transparency and internal governance. It concludes that Taiwan Biobank’s conflict-ridden evolution represents a cautionary tale, an example of how not to develop a flagship resource.